(untitled) (Journal of Environmental Science and Natural Resources, 2015)
The study was conducted to know the status of water quality of the Ramna, Crescent and Hatirjheel lakes in the Dhaka city. Water samples were collected from three different points of each lake and analyzed for various physicochemical parameters including temperature, pH, EC, TDS, DO, BOD, hardness, alkalinity, acidity during the period from November 2013 to April 2014. The mean temperature 22.54, 24.59 and 24.24°C; EC 15400, 282.00 and 618.27 ?Scm-1; TDS 85.38, 155.60 and 339.90 ppm; pH 7.73, 7.85 and 7.67; DO 3.51, 3.92 and 3.65 ppm; BOD 0.93, 0.73 and 3.15 ppm; hardness 95.00, 108.56 and 105.11 ppm; alkalinity 48.9, 120.7 and 249.1 ppm, and acidity 2.18, 2.67 and 2.05 ppm were investigated from Ramna, Crescent and Hatirjheel lakes, respectively. Lower concentration of DO was observed in all three lakes that severely harmed the aquatic organisms and degrade their habitat. The comparative study demonstrated that the concentration of BOD, EC, TDS, alkalinity and acidity of Hatirjheel Lake was higher than Ramna and Crescent lakes which indicated pollution of the lake water. The rain and storm water runoff, lack of awareness of people were responsible for the pollution of Ramna, Crescent and Hatirjheel lakes water. Connection of the sewerage line with the rain water collection channels and mixing of solid waste with lake water are the main reasons for pollution of Hatirjheel lake. Poor water quality of these lakes affects the ecosystem and aesthetic beauty negatively. To maintain the sound environment and healthy ecosystem of the lakes and the surrounding areas need proper management and monitoring and implementation of existing laws and regulations. Moreover public awareness is necessary otherwise it is hardly possible to maintain sound water quality of these three lakes. J. Environ. Sci. & Natural Resources, 8(1): 1-5 2015